Does the green finance reform and innovation experimental zone policy reduce carbon emission intensity? Evidence from Chinese cities - Yang, Yun; Peng, Chunli (Frontiers in Energy Research, 2024)
The reduction of carbon emission intensity cannot be achieved without policy support, of which green financial policy is a major component. The main aim of this study is to discuss the causality between the green finance reform and innovation (GFRI) experimental zone policy and the intensity of carbon emissions in China. Using data from 265 Chinese cities from 2005 to 2021, this study applies a time-varying difference-in-differences (DID) model to assess the effect of the GFRI experimental zone policy on the intensity of carbon emissions. The heterogeneity of impacts and the parallel-serial mediation effect of this experimental zone policy are discussed further. The following main findings are obtained. (1) The GFRI experimental zone policy dramatically reduces carbon emission intensity, and this effect is more prominent in cities with large sizes of credit and bond finance. (2) After considering the heterogeneity of government environmental concerns and fiscal pressures, this study reveals that the effect of the GFRI experimental zone policy on reducing carbon emission intensity is weaker in cities with high numbers of environmental protection penalties and fiscal pressures. As the number of environmental penalties and fiscal pressures increases, the effect of the GFRI experimental zone policy on reducing carbon emission intensity decreases; that is, the phenomenon of environmental protection paradoxes and policy conflicts has emerged. (3) Increasing financing for green projects and decreasing the energy intensity of the industry are the primary mediating channels for GFRI experimental zone policy to reduce carbon emission intensity, but the mediating channels for boosting green innovation and promoting energy structure adjustment are not prominent. Moreover, the total effect of the GFRI experimental zone policy on reducing carbon emission intensity is 72% direct and more than 20% indirect. This study concludes that in regions with high fiscal pressure, governments should rely more on green finance to decrease carbon emission intensity. Meanwhile, a green finance policy must be more supportive of zero-carbon energy production and reduce direct environmental penalties to decrease carbon emission intensity in the future.